Detection of multiple viruses potentially infecting humans in sewage water from Xinjiang Uygur Autonomous Region, China - Yang, Qian; Rivailler, Pierre; Zhu, Shuangli; Yan, Dongmei; Xie, Na; Tang, Haishu; Zhang, Yong; Xu, Wenbo (The Science of the total environment, 2021)
The progress of sequencing technologies has facilitated metagenomics projects on environmental samples like sewage water. The present study concerned the analysis of sewage samples collected from 3 locations in Xinjiang Uygur Autonomous Region in China. The analysis focused on RNA viruses known to infect humans and identified viruses from 10 families. The proportion of human virus species in the sewage samples was relatively stable with an average of 17%. Thirty virus species known to infect humans were identified and they belonged to 6 families: Picornaviridae (12), Astroviridae (11), Reoviridae (3), Caliciviridae (2), Papillomaviridae (1) and Picobirnaviridae (1). A total of 16 full-length genomes were generated from Astroviridae, Picornaviridae (Salivirus and Kobuvirus) and Picobirnaviridae. Astroviruses appeared to be the most present viruses and were detected in all sewage samples. Analyzing the virome of sewage samples should help to monitor any potential risks to public health. [Display omitted] •Metagenomics analysis of sewage samples•Samples collected in Xinjiang Uygur Autonomous Region, China•Detection of sequences from RNA viruses likely to infect humans•Astroviridae detected in all 7 samples (3 locations, 3 collection times)•Detection of viruses with potential health risk